2013
DOI: 10.1104/pp.112.211144
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation of Arabidopsis Root Architecture Reveals Complementing Adaptive Strategies to Potassium Starvation      

Abstract: Root architecture is a highly plastic and environmentally responsive trait that enables plants to counteract nutrient scarcities with different foraging strategies. In potassium (K) deficiency (low K), seedlings of the Arabidopsis (Arabidopsis thaliana) reference accession Columbia (Col-0) show a strong reduction of lateral root elongation. To date, it is not clear whether this is a direct consequence of the lack of K as an osmoticum or a triggered response to maintain the growth of other organs under limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 51 publications
(77 reference statements)
5
95
3
Order By: Relevance
“…Until now, a detailed examination of the effects of nutrient deficiencies on RSA has been fragmented or totally absent. In fact, only P, N, and, very recently, K deficiency-induced modifications of RSA were more exhaustively assessed in Arabidopsis (Linkohr et al, 2002;Sanchez-Calderon et al, 2005;Kellermeier et al, 2013). In other cases, although the effects of nutrient deficiencies on root development have been reported (for review, see López-Bucio et al, 2003;Nibau et al, 2008), these effects were either restricted to root hair formation (e.g.…”
Section: A Detailed Protocol For Obtaining Nutrient-deficient Solid Mmentioning
confidence: 99%
“…Until now, a detailed examination of the effects of nutrient deficiencies on RSA has been fragmented or totally absent. In fact, only P, N, and, very recently, K deficiency-induced modifications of RSA were more exhaustively assessed in Arabidopsis (Linkohr et al, 2002;Sanchez-Calderon et al, 2005;Kellermeier et al, 2013). In other cases, although the effects of nutrient deficiencies on root development have been reported (for review, see López-Bucio et al, 2003;Nibau et al, 2008), these effects were either restricted to root hair formation (e.g.…”
Section: A Detailed Protocol For Obtaining Nutrient-deficient Solid Mmentioning
confidence: 99%
“…For the latter, seeds were germinated on agar plates and 2-to 3-week-old seedlings were placed in perforated lids of black 0.7-liter plastic containers. The growth medium consisted of a minimal sufficient nutrient medium (Kellermeier et al, 2013). For salt treatment, NaCl powder was stirred directly into the growth container to obtain the desired concentration (as stated in the figures).…”
Section: Growth Conditions and Treatmentsmentioning
confidence: 99%
“…We focused on the 0.5-cm root constraint, as this is the weakest treatment, suggesting that it should have the fewest indirect physiological effects, and as it also had a positive growth effect on the Bay accession. Furthermore, previous research has shown that the Bay and Sha parents and RILs have a root growth rate that would allow the seedlings' roots to grow below this constraint barrier within 24 h of germination (Loudet et al, 2005;Bouteillé et al, 2012;Kellermeier et al, 2013). Additionally, the soil within this constraint was packed to the same level as the surrounding soil and the constraint did not restrict the flow of water or oxygen given the surface-to-volume ratio.…”
Section: Genetic Regulation Of Response To Root Constraintmentioning
confidence: 99%